From Target Identification to Drug Development in Space: Using the Microgravity Assist - Braddock, Martin (Current Drug Discovery Technologies, 2020)
The unique nature of microgravity encountered in space provides an opportunity for drug discovery and development that cannot be replicated on Earth. From the production of superior protein crystals to the identification and validation of new drug targets to microarray analyses of transcripts attenuated by microgravity, there are numerous examples which demonstrate the benefit of exploiting the space environment. Moreover, studies conducted on Space Shuttle missions, the International Space Station and other craft have had a direct benefit for drug development programmes such as those directed against reducing bone and muscle loss or increasing bone formation. This review will highlight advances made in both drug discovery and development and offer some future insight into how drug discovery and associated technologies may be further advanced using the microgravity assist.
Keywords: target identification